2017
DOI: 10.1021/acs.energyfuels.7b00107
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Electrostatic Precipitation of Low-Resistivity High-Carbon Fly Ash at High Temperature

Abstract: A high-temperature electrostatic precipitator (ESP) is a good solution for hot gas cleaning to ensure the long-term stability of the production system in many energy-consuming industries. The high-carbon fly ash particles in the gasification of coal pyrolysis process are typical particles with low resistivity. In this paper, the characteristics of the coal pyrolysis furnace fly ash (ash A) were compared with coal-fired power plant fly ash (ash B). The effects of their characteristics on particle removal were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Furthermore, they are recently applied for PM reduction in the exhaust gas of diesel engines [77], for small-scale biomass furnaces [78], in coal pyrolysis furnaces and coal-fired power plants to reduce fly ash [79], etc. In Ref.…”
Section: Electrostatic Precipitation (Esp)mentioning
confidence: 99%
“…Furthermore, they are recently applied for PM reduction in the exhaust gas of diesel engines [77], for small-scale biomass furnaces [78], in coal pyrolysis furnaces and coal-fired power plants to reduce fly ash [79], etc. In Ref.…”
Section: Electrostatic Precipitation (Esp)mentioning
confidence: 99%
“…A constant 10 cm s À1 air ow is chosen because it is a typical condition chosen in the literatures. 23,48,49 For both modes, the spatial and temporal dispersions of PM are monitored using a home-made laser light scattering setup, as described below.…”
Section: Generation Of Pm and Operating Modementioning
confidence: 99%
“…Air pollution has become one of the most serious environmental issues in China, especially particulate matter pollution. The particulate matter emitted by coal-fired power plants is one of the main pollution sources [1,2,3,4,5,6]. Currently, with the increasingly rigorous emission standards [7], the accuracy of real-time measurement of particulate matter mass concentrations should be improved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Chen et al [23] experimentally demonstrated the sensitivity of mass concentration changes with particle size at any detection angle. In coal-fired power plants, the size of particles varies with time due to the coal type, combustion condition, boiler load, and precipitator performance [6,24,25]. In these cases, the particles emitted from the stack are mainly 0.1 to 10 μm in size and the mass is concentrated in the micro size range [24,26,27].…”
Section: Introductionmentioning
confidence: 99%